Identity economics : how our identities shape our work, wages, and well-being - Akerlof, George A., 1940-; Kranton, Rachel E. (Princeton University Press, 2010)
Identity Economics provides an important and compelling new way to understand human behavior, revealing how our identities--and not just economic incentives--influence our decisions. In 1995, economist Rachel Kranton wrote future Nobel Prize-winner George Akerlof a letter insisting that his most recent paper was wrong. Identity, she argued, was the missing element that would help to explain why people--facing the same economic circumstances--would make different choices. This was the beginning of a fourteen-year collaboration--and of Identity Economics. The authors explain how our conception o.